On the defect of nondenseness of continuous imbeddings in the scale of Hilbert spaces - Bozhok, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain a formula for the determination of a defect under a continuous imbedding of subspaces in the scale of Hilbert spaces.